Research on mathematical beliefs: systematic literature review - Muhtarom Muhtarom; Sutrisno Sutrisno; Nizaruddin Nizaruddin; Yanuar Hery Murtianto (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study uses the systematic literature review (SLR) method to identify knowledge trends in beliefs about the nature of mathematics, learning mathematics and identify new development opportunities for further research. The Scopus database was used, and 41 documents were found as the primary source for further analysis. The results show that mathematical beliefs have become a current research trend. The number of publications increased significantly starting in 1989, accompanied by many citations. Based on these primary documents, it is known that the development of mathematical beliefs research topics. The foundation of this topic begins with studying the topic of knowledge, activities, and learning mathematics. Then it is developed into other, more varied studies, including teacher’s beliefs transition; mathematical beliefs comparison; mathematics teacher’s belief, teaching, and learning; mathematical beliefs and problem-solving; inquiry-based learning (IBL); affective factors; technology utilization; common misconceptions; and development of mathematics teacher’s beliefs instrument. This research investigates the core of scientific work to provide information to researchers and institutions as material for consideration of research to be carried out.